Efeito do revestimento à base de gelatina extraída de escamas de Oreochromis niloticus na avaliação da qualidade de Penaeus vannamei congelado - Nogueira, Sara Monaliza Sousa (2024)
The gelatin coating extracted from Nile tilapia scales is a renewable technology with excellent benefits for the preservation of fishery products of high commercial value. This research aimed to evaluate the quality and shelf life of shrimp Penaeus vannamei coated with gelatin extracted from Nile tilapia scales (Oreochromis niloticus), stored frozen at -18°C for 180 days. For this, gelatin was extracted from Nile tilapia scales, lyophilized, characterized by physicochemical analysis (pH, color, gel strength, centesimal composition, DSC and FTIR), the application by spraying of gelatinous solution at 1.5% and 0.2% of glycerol in peeled and headless shrimp (treatment with gelatin – G) and the determination of the quality of these coated and uncoated shrimp (control – C) through microbiological and physical-chemical analyzes (determination of pH, TVB-N, TMA-N and TBARS), at the initial moment and then every 30 days for 6 months, and the last two analyzes every 90 days (T0, T1, T2, T3, T4, T5, T6, T9 and T12 months). The results showed that the gelatin obtained had good physicochemical characteristics and that its coating solution was effective in reducing shrimp deterioration in terms of microbiological parameters, pH, TVB-N, TMA-N and lipid oxidation. It was concluded that the use of this coating combined with frozen storage can be a suitable alternative to maintain the quality of shrimp for long term.